Trying to fit in – Upper secondary school students' negotiation processes between sports culture and youth culture. (June 2019) - Nielsen, Stine Frydendal; Thing, Lone Friis
In this paper we present results concerning how students in a Danish upper secondary school negotiate between sports culture and the prevailing norms of youth culture in a local school context. The study shows that it can be rather difficult for young people to combine sports culture with the local youth culture, because living a healthy and physically active life doesn't fit very well with the prevailing norms of youth culture, which involve a dominant social arena characterized by parties and alcohol. By applying the figurational sociology of Norbert Elias, this article shows that being included in a sports figuration can result in exclusion from the youth figuration. Young athletic students are therefore in a constant process of negotiation, where they struggle to fit into both sport and non-sport related contexts, because it is important to belong within both. The study is based on 16 focus group interviews [N=120] conducted over four years in one Danish upper secondary school.